Axonal pathology in patients with multiple sclerosis: Evidence from in vivo proton magnetic resonance spectroscopy - Narayanan,S; Caramanos,Z; Matthews,PM; Arnold,DL (2011)
Introduction The clinical course of multiple sclerosis (MS) is highly variable, and pathological changes that are seen with the disease are heterogeneous amongst individuals. In recent years, there has been increasing interest in the development of magnetic resonance imaging (MRI) approaches to characterizing the pathological substrates of disability in MS with the objective of developing quantitative in vivo indices of pathology that could provide new insights into the pathogenesis of the disease, as well as provide more specific or sensitive end-points for treatment trials. This chapter reviews results from studies that have used either proton magnetic resonance spectroscopy (1H-MRS, a technique that allows for the acquisition of 1H-MR spectra from single voxels) or 1H-MR spectroscopic imaging (1H-MRSI, a technique that allows for the simultaneous acquisition of 1H-MR spectra from multiple voxels) to measure in vivo chemical pathology associated with impairment of axonal metabolic or structural integrity, and places these results in the context of relevant histopathological investigations. We will focus on an important hypothesis that has developed from these studies: that axonal pathology is central to the final common pathway leading to the progressive disability that is seen in individuals with this disease.